Discrete Determinants in ArfGAP2/3 Conferring Golgi Localization and Regulation by the COPI Coat - Kliouchnikov, Lena (The American Society for Cell Biology, 2009)
From yeast to mammals, two types of GTPase-activating proteins, ArfGAP1 and ArfGAP2/3, control guanosine triphosphate (GTP) hydrolysis on the small G protein ADP-ribosylation factor (Arf) 1 at the Golgi apparatus. Although functionally interchangeable, they display little similarity outside the catalytic GTPase-activating protein (GAP) domain, suggesting differential regulation. ArfGAP1 is controlled by membrane curvature through its amphipathic lipid packing sensor motifs, whereas Golgi targeting of ArfGAP2 depends on coatomer, the building block of the COPI coat. Using a reporter fusion approach and in vitro assays, we identified several functional elements in ArfGAP2/3. We show that the Golgi localization of ArfGAP3 depends on both a central basic stretch and a carboxy-amphipathic motif. The basic stretch interacts directly with coatomer, which we found essential for the catalytic activity of ArfGAP3 on Arf1-GTP, whereas the carboxy-amphipathic motif interacts directly with lipid membranes but has minor role in the regulation of ArfGAP3 activity. Our findings indicate that the two types of ArfGAP proteins that reside at the Golgi use a different combination of protein–protein and protein–lipid interactions to promote GTP hydrolysis in Arf1-GTP.